Blues all around me the autobiography of B.B. King - King, B. B. (Sceptre, 1997)
"Riley B. King grew up amidst the cotton farms of Mississippi, picking in the fields. At age 21 he wrecked a tractor and took it as a sign that a brighter future awaited him as a musician in Memphis. The rest is history." "Recounting his days as a disk jockey and pioneering bluesman on the rhythm and blues circuit, B. B. dramatizes his whirlwind adventures, from the Memphis of the forties to the Moscow of the nineties, in a voice that is both raw and real. A deeply sensuous and sensitive soul, he discloses his complex relationship to women and sexuality, and chronicles his first-hand experience with racism, the Civil Rights movement, and the shifting politics of show business."--BOOK JACKET.